Redefining Regional Supervisory Authority: Smart Eco Supervision as a Preventive Administrative Sanction Instrument - Podungge, Abdul Madjid; Badu, Risti Ristianingsih; Podungge, Abdul Wahab; Hunawa, Robby (Actual Insight, 2025)
This study investigates the critical development paradox in Gorontalo, where a 6.07% extractive-driven economic growth inversely correlates with extreme mercury contamination (Igeo) and severe environmental degradation in river basins. This systemic issue stems from acute regulatory discord caused by centralized licensing under the Minerba and Job Creation Laws, creating a supervisory authority vacuum that effectively paralyzes regional oversight mechanisms. Adopting a constructive socio-legal approach triangulated with hybrid spatial data (NDVI/SAR), this article proposes the Smart Eco Supervision model to bridge the critical gap between technical surveillance and legal enforcement. This model integrates high-precision geospatial detection to provide indisputable objective evidence for State Administrative Officers (TUN). Furthermore, it legally reconstructs sanctions into Restorative Administrative Sanctions, mandating scientifically quantifiable restoration methods like phytoremediation instead of mere financial fines. Grounded in Salus Populi Suprema Lex Esto, this framework redefines regional authority by prioritizing citizens' ecological safety as the supreme law, ensuring substantive environmental justice for impacted communities.